Perbedaan Kelelahan Karyawan Bagian Maintenance Sebelum Dan Setelah Intervensi Kebugaran Fisik Sebagai Bagian Dari Promosi Kesehatan PT. X - Permana, Iman (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2010)
Background: Fatigue at work could affect the productivity of the employees. A good physical fitness is one way to diminish the level of fatigue at work. Moreover, by exercising in a good and proper way, employees could increase their status of physical fitness. From the initial research in PT X, almost half (47,37%) of the respondents had their physical fitness status below the â€œgoodâ€ level and 36,8% of them had never been exercising before. On the other hand, the company had built a good and quite complete sport facility. Method: A one-group pre and post test design was used to measure the fatigue level of all respondents after performing an aerobic fitness program for 2 weeks in February 2009 with a two daily interval and about 30 â€“ 40 minutes of duration. The fatigue level data was collected by using a modified Kuesioner Alat Ukur Kelelahan Kerja (Questioners for Measuring the Level of Fatigue at Work) by Lientje S. The Chester Step test was used to measure the level of fitness. The number of population was 102 with 10 employees as the sample of research, which 2 of them were excluded from the test due to the incomplete data. The Wilcoxon Signed Ranks test was used to test the data. The same test was used to determine the difference of the fitness level before and after the aerobic program. Spearman Ranks Test was used to determine the correlation between the age and the level of fatigue and between age and the level of fitness. The same test was also used to measure the correlation between the fitness level and the fatigue level. Result:. There was no difference in the level of fatigue among the respondents before and after the aerobic fitness program, (p 0,574, Ã¡ 95%). There was an improvement of the physical fitness level (Z -2,043, p 0,05). There were no correlation between age and the level of fatigue (p -0,405) and between age and the level of physical fitness (p -0,220). There was no correlation between the level of fitness and the level of fatigue after performing the physical fitness program (p < 0,005).